2018
DOI: 10.1177/0733464818787716
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Utilization Among Chinese American Older Adults: Moderation of Social Support With Functional Limitation

Abstract: In this study, we aimed to examine the relationship of social support with hospitalizations and emergency department (ED) visits among older Chinese adults in the United States and its possible mechanism. This was a secondary analysis of data from the Population Study of Chinese Elderly (July 2011-June 2013; N = 3,157). After adjusting for demographic, clinical, and functional covariates in logistic regression analyses, significant interaction between social support from spouse and the number of functional lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, higher depressive symptoms were found to be associated with increased outpatient resource utilization and more visits to family physicians (Bentur and Heymann, 2020). Finally, in the current study coping resources included optimism (an internal resource) and social support (an external resource), as these coping resources were found to be significantly associated with health services consumption (DeViva et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 58%
“…Furthermore, higher depressive symptoms were found to be associated with increased outpatient resource utilization and more visits to family physicians (Bentur and Heymann, 2020). Finally, in the current study coping resources included optimism (an internal resource) and social support (an external resource), as these coping resources were found to be significantly associated with health services consumption (DeViva et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 58%
“…Another study conducted in Ireland and the USA found similar results, which stated that not having a spouse or not living with a spouse is strongly associated with impairment in functional abilities 21,22 . There is also a study in China that found that older persons who are not married showed significant functional decline in old age 23 . On the other hand, another study in China showed that married older persons with children are at higher risk of limitation in daily living because they have to cope with their adult children's demands, which might exceed their coping resources 24 .…”
Section: Discussionmentioning
confidence: 73%
“…21,22 There is also a study in China that found that older persons who are not married showed significant functional decline in old age. 23 On the other hand, another study in China showed that married older persons with children are at higher risk of limitation in daily living because they have to cope with their adult children's demands, which might exceed their coping resources. 24 However, the influence of social support on activity limitation in our study was independent of the presence of a spouse, unlike the findings of the above two studies.…”
Section: Discussionmentioning
confidence: 99%
“…The one quantitative study from Canada examined help-seeking attitudes and mental health-care utilisation; it did not find a significant association (Tieu and Konnert, 2014). Six studies analysed the same dataset, the Population Study of Chinese Elderly in Chicago (PINE study) (Dong and Liu, 2017;Wang et al, 2018;Guo et al, 2019;Hei et al, 2019;Kong et al, 2019;Wang et al 2022) and so had similar findings.…”
Section: Quantitative Findingsmentioning
confidence: 96%